Molecular MR-Imaging for Noninvasive Quantification of the Anti-Inflammatory Effect of Targeting Interleukin-1β in a Mouse Model of Aortic Aneurysm. (20th November 2020) - Brangsch, Julia; Reimann, Carolin; Kaufmann, Jan Ole; Adams, Lisa Christine; Onthank, David; Thöne-Reineke, Christa; Robinson, Simon; Wilke, Marco; Weller, Michael; Buchholz, Rebecca; Karst, Uwe; Botnar, Rene; et al.
Background: Molecular-MRI is a promising imaging modality for the assessment of abdominal aortic aneurysms (AAAs). Interleukin-1β (IL-1β) represents a new therapeutic tool for AAA-treatment, since pro-inflammatory cytokines are key-mediators of inflammation. This study investigates the potential of molecular-MRI to evaluate therapeutic effects of an anti-IL-1β-therapy on AAA-formation in a mouse-model. Methods: Osmotic-minipumps were implanted in apolipoprotein-deficient-mice (N = 27). One group (Ang-II+01BSUR group, n = 9) was infused with angiotensin-II (Ang-II) for 4 weeks and received an anti-murine IL-1β-antibody (01BSUR) 3 times. One group (Ang-II-group, n = 9) was infused with Ang-II for 4 weeks but received no treatment. Control-group (n = 9) was infused with saline and received no treatment. MR-imaging was performed using an elastin-specific gadolinium-based-probe (0.2 mmol/kg). Results: Mice of the Ang-II+01BSUR-group showed a lower aortic-diameter compared to mice of the Ang-II-group and control mice (p < 0.05). Using the elastin-specific-probe, a significant decrease in elastin-destruction was observed in mice of the Ang-II+01BSUR-group. In vivo MR-measurements correlated well with histopathology (y = 0.34x-13.81, R 2 = 0.84, p < 0.05), ICP-MS (y = 0.02x+2.39; R 2 = 0.81, p < 0.05) and LA-ICP-MS. Immunofluorescence and western-blotting confirmed a reduced IL-1β-expression. Conclusions: Molecular-MRI enables the early visualization and quantification of the anti-inflammatory-effects of an IL-1β-inhibitor in a mouse-model of AAAs. Responders and non-responders could be identified early after the initiation of the therapy using molecular-MRI.